2004
DOI: 10.1017/s1474747204001684
|View full text |Cite
|
Sign up to set email alerts
|

Cash balance pension plan conversions and the new economy

Abstract: Many firms that sponsor traditional defined benefit pensions have converted their plans to cash balance plans in the last ten years. Cash balance plans combine features of defined benefit (DB) and defined contribution (DC) plans, and yet their introduction has proven considerably more controversial than has the increasing popularity of DC plans. The goal of this study is to estimate a hierarchy of the influences on the decision of a firm to convert its traditional defined benefit pension plan to a cash balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…Some have suggested that firms were converting to CB plans instead of incurring these costs, especially after the IRS increased the excise tax in 1990 (Clark et al 2001;Coronado and Copeland 2004;Niehaus and Yu 2005;D'Souza et al 2006 …”
Section: Tax Avoidancementioning
confidence: 99%
See 3 more Smart Citations
“…Some have suggested that firms were converting to CB plans instead of incurring these costs, especially after the IRS increased the excise tax in 1990 (Clark et al 2001;Coronado and Copeland 2004;Niehaus and Yu 2005;D'Souza et al 2006 …”
Section: Tax Avoidancementioning
confidence: 99%
“…Clark et al (2001) examine conversions in 1996 and find no difference in the funding levels of cash balance plans and traditional DB plans. Coronado and Copeland (2004) find that 16 of the 32 cash balance plans in their sample were over-funded prior to conversion, as measured by the projected benefit obligation (PBO) 4 . However, when they use a broader sample (316 S&P 500 firms that sponsor a DB plan), they find no effect of the funding ratio on the probability of conversion (Coronado and Copeland 2004).…”
Section: Present Value Of Benefitmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronado and Copeland (2003) offer another perspective on the reasons for the shift to cash balance plans. They contend that these conversions occurred in competitive industries with tight labor markets, and were done largely to improve compensation for a more mobile workforce.…”
Section: Some Researchers (Seementioning
confidence: 99%